Cross-Validation of the Spanish HP-Version of the Jefferson Scale of Empathy Confirmed with Some Cross-Cultural Differences - Alcorta-Garza, Adelina; San-Martín, Montserrat; Delgado-Bolton, Roberto; Soler-González, Jorge; Roig, Helena; Vivanco, Luis (Frontiers in Psychology, 2016)
Context: Medical educators agree that empathy is essential for physicians’ professionalism. The Health Professional Version of the Jefferson Scale of Empathy (JSE-HP) was developed in response to a need for a psychometrically sound instrument to measure empathy in the context of patient care. Although extensive support for its validity and reliability is available, the authors recognize the necessity to examine psychometrics of the JSE-HP in different socio-cultural contexts to assure the psychometric soundness of this instrument. The first aim of this study was to confirm its psychometric properties in the cross-cultural context of Spain and Latin American countries. The second aim was to measure the influence of social and cultural factors on the development of medical empathy in health practitioners. Methods: The original English version of the JSE-HP was translated into International Spanish using back-translation procedures. The Spanish version of the JSE-HP was administered to 896 physicians from Spain and thirteen Latin American countries. Data were subjected to exploratory factor analysis using principal component analysis with oblique rotation (promax) to allow for correlation among the resulting factors, followed by a second analysis, using confirmatory factor analysis. Two theoretical models, one based on the English JSE-HP and another on the first Spanish student version of the JSE (JSE-S), were tested. Demographic variables were compared using group comparisons. Results: A total of 715 (80%) surveys were returned fully completed. Cronbach’s alpha coefficient of the JSE for the entire sample was 0.84. The psychometric properties of the Spanish JSE-HP matched those of the original English JSE-HP. However, the Spanish JSE-S model proved more appropriate than the original English model for the sample in this study. Group comparisons among physicians classified by gender, medical specialties, cultural and cross-cultural backgrounds yielded statistically significant differences (p<0.001). Conclusions: The findings support the underlying factor structure of the Jefferson Scale of Empathy. The results reveal the importance of culture in the development of medical empathy. The cross-cultural differences described could open gates for further lines of medical education research.